2013
DOI: 10.2215/cjn.09580911
|View full text |Cite
|
Sign up to set email alerts
|

PTH—A Particularly Tricky Hormone

Abstract: SummaryPlasma parathyroid hormone (PTH) concentrations are commonly measured in the context of CKD, as PTH concentration elevation is typical in this clinical context. Much has been inferred from this raised PTH concentration tendency, both about the state of skeletal integrity and health and also about the potential clinical outcomes for patients. However, we feel that reliance on PTH concentrations alone is a dangerous substitute for the search for, and use of, more precise and reliable biomarkers. In this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 89 publications
(65 reference statements)
4
76
0
Order By: Relevance
“…31 The importance of PTH as a biomarker of abnormal bone is controversial. 32,33 Cohort studies have shown an increased risk of fracture associated with low PTH 12,29,30 or very high PTH. 3,12,30,34 Some studies have found no significant relation to PTH.…”
Section: Discussionmentioning
confidence: 99%
“…31 The importance of PTH as a biomarker of abnormal bone is controversial. 32,33 Cohort studies have shown an increased risk of fracture associated with low PTH 12,29,30 or very high PTH. 3,12,30,34 Some studies have found no significant relation to PTH.…”
Section: Discussionmentioning
confidence: 99%
“…The application of these newer analytical platforms to clinical cohorts is awaited, and independent validation is required. (32,33). Nonetheless, such experience with other mineral metabolism analytes should prompt attempts to harmonize FGF23 assay readout.…”
Section: Analytical Considerations Of Fgf23 Measurementmentioning
confidence: 99%
“…Given the many other factors that influence clinical interpretation of PTH results (e.g., between-method differences, specificity) [48], laboratory professionals should ensure samples are appropriately stored. Based on the evidence reviewed here, the following recommendation seems appropriate:…”
Section: We Recommend Blood Samples For Pth Measurement Should Be Takmentioning
confidence: 99%